Encyclopedia of Data Warehousing and Mining, Second Edition 2009
DOI: 10.4018/978-1-60566-010-3.ch168
|View full text |Cite
|
Sign up to set email alerts
|

On Interactive Data Mining

Abstract: INTRODUCTIONExploring and extracting knowledge from data is one of the fundamental problems in science. Data mining consists of important tasks, such as description, prediction and explanation of data, and applies computer technologies to nontrivial calculations. Computer systems can maintain precise operations under a heavy information load, and also can maintain steady performance. Without the aid of computer systems, it is very difficult for people to be aware of, to extract, to search and to retrieve knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…User-friendly data mining has emerged as a challenge in recent bibliography related to support novice data miners. Some user-friendly approaches are focused on providing interactive systems, an adaptive and effective communication between human users and computer systems [28] where the user is guided through the data mining process. FIU-Miner [29], is an integrated system that facilitates users to conduct ad-hoc data mining tasks.…”
Section: Related Workmentioning
confidence: 99%
“…User-friendly data mining has emerged as a challenge in recent bibliography related to support novice data miners. Some user-friendly approaches are focused on providing interactive systems, an adaptive and effective communication between human users and computer systems [28] where the user is guided through the data mining process. FIU-Miner [29], is an integrated system that facilitates users to conduct ad-hoc data mining tasks.…”
Section: Related Workmentioning
confidence: 99%
“…The three-layered conceptual framework represents the understanding, discovery, and utilization of knowledge, and can be easily extended to a user-centered conceptual framework for interactive data mining (Zhao, 2007). The user-centered three-layered framework consists of the philosophy layer, the technique layer, and the application layer, and considers one important factor, user requirements and preferences.…”
Section: A Framework Of Interactive Data Miningmentioning
confidence: 99%
“…According to the above observations, we believe that interactive systems are required for data mining tasks. Though human-machine interaction has been emphasized for many disciplines, it did not receive enough attention in the domain of data mining until recently (Brachmann & Anand, 1996;Han, Hu & Cercone, 2003;Zhao, 2007;Zhao & Yao, 2005). Generally, an interactive data mining system is an integration of a human user and a computer.…”
mentioning
confidence: 99%
“…Data mining (DM) techniques have been used in various studies for exploring patterns from complex and large datasets where it has been found to be less time consuming than other approaches (Zaki et al 2010). DM refers to the process of extracting meaningful patterns that were previously unknown and "hidden" in the data (Baker 2010, Zhao andYao 2005). In a context of ever-increasing wind data and with pressing needs for turning this data into useful information (e.g.…”
Section: Mining Wind Patterns: a Multi-dimensional Perspectivementioning
confidence: 99%